A methodology to measure the degre of managerial innovation - Mustafa Batuhan Ayhan; Ercan Oztemel (Journal of Industrial Engineering and Management, 2014)
Purpose: The main objective of this study is to introduce the concept of managerial innovation and to propose a quantitative methodology to measure the degree of managerial innovation capability by analyzing the evolution of the techniques used for management functions. Design/methodology/approach: The methodology mainly focuses on the different techniques used for each management functions namely; Planning, Organizing, Leading, Controlling and Coordinating. These functions are studied and the different techniques used for them are listed. Since the techniques used for these management functions evolve in time due to technological and social changes, a methodology is required to measure the degree of managerial innovation capability. This competency is measured through an analysis performed to point out which techniques used for each of these functions. Findings: To check the validity and applicability of this methodology, it is implemented to a manufacturing company. Depending on the results of the implementation, enhancements are suggested to the company for each function to survive in the changing managerial conditions Research limitations/implications: The primary limitation of this study is the implementation area. Although the study is implemented in just a single manufacturing company, it is welcomed to apply the same methodology to measure the managerial innovation capabilities of other manufacturing companies. Moreover, the model is ready to be adapted to different sectors although it is mainly prepared for manufacturing sector. Originality/value: Although innovation management is widely studied, managerial innovation is a new concept and introduced to measure the capability to challenge the changes occur in managerial functions. As a brief this methodology aims to be a pioneer in the field of managerial innovation regarding the evolution of management functions. Therefore it is expected to lead more studies to inspect the progress of change throughout the history and the future trends.